Investigating personal and clinical recovery processes in people with first episode psychosis. Issue 10 (25th November 2021) - Austin, Stephen F.; Hjorthøj, Carsten; Baagland, Helle; Simonsen, Erik; Dam, Jesper
Abstract: Introduction: Schizophrenia is a serious mental illness characterized by a range of symptoms such as distortions in reality, emotional abnormalities and deficits in cognition. Recovery from severe mental illness can be conceptualized in a number of ways. Clinical recovery has a focus on symptoms and functioning whilst personal recovery describes the process of developing new meaning and purpose in life beyond mental illness. Objective: This longitudinal study examined the relationship between clinical and personal recovery processes within a group of people with first episode psychosis (FEP) receiving early intervention treatment over a period of up to 2 years. Methods: The study sequentially recruited people with FEP that accepted into early intervention treatment. Participants were evaluated at baseline, 12 months and completion of treatment for clinical and personal recovery. Results: A total of 51 participants were recruited, completed treatment and assessments. Modest but significant correlations (r = 0.38–0.51) were found between personal recovery and certain aspects of clinical recovery (negative symptoms and functioning). Improvements in functioning (vocational and social activities) predicted both personal and clinical recovery whilst negative symptoms predicted attaining clinical recovery. Reductions in negative symptoms (global, apathy and anhedonia) during treatment were associated with moving towards personal recovery. Psychotic symptoms were not significantly associated with the attainment of clinical or personal recovery. Conclusions: Results indicated that clinical and personal recovery are interdependent and complementary processes. Mental health services may need implement interventions that simultaneously target clinical and personal recovery processes in order to meet the treatment needs of people with psychosis.